2019
DOI: 10.15171/ipp.2020.02
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with delayed diagnosis of breast cancer; a study in North-West of Iran

Abstract: Introduction: Delayed diagnosis and treatment of breast cancer leads to the presentation of the disease in advanced stages necessitating more invasive surgical interventions, increasing health care costs and mortality rate, and finally reduced patients’ survival. Objectives: This study aimed to investigate the factors associated with delayed diagnosis of breast cancer in the north-west of Iran. Patients and Methods: This retrospective cross-sectional study was conducted on 70 breast cancer patients referred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Another study conductedby Nasrin and colleagues reported a mean age of 43.7 years with the maximum age of 71 and minimum age of 14 years and most women fell in the age bracket of 40 to 60 in her study While Bariati et al, patients aged above 59 were 50% in his study [3,7]. In our study, we found that 56% of patients reported a delay of more than 3 months and about 28% were at the early stage and 29% at the advanced stage while in Germany, the UK, and Columbia about 17% of patients reported similar delay [8].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Another study conductedby Nasrin and colleagues reported a mean age of 43.7 years with the maximum age of 71 and minimum age of 14 years and most women fell in the age bracket of 40 to 60 in her study While Bariati et al, patients aged above 59 were 50% in his study [3,7]. In our study, we found that 56% of patients reported a delay of more than 3 months and about 28% were at the early stage and 29% at the advanced stage while in Germany, the UK, and Columbia about 17% of patients reported similar delay [8].…”
Section: Discussionmentioning
confidence: 69%
“…Due to the high mortality rate in women, diagnostic procedures are of prime importance for breast cancers because many people visit for consultations in advance stages of the disease. Many people present late due to fear of cancer, educational background or lack of support from family and friends and some don't have access to medical facilities [3]. Breast cancer is examined by a visual inspection with patients sitting upright and changes in nipples, asymmetry, skin dimpling, erythema, and obvious masses are noted in the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information about each article is included in Table S1. The majority of articles reported on studies conducted in countries in Africa (32%), 22–37 followed by South‐East Asia (30%), 38–51,71 the Middle East (20%), 52–61 Latin America (16%), 62–69 and Eastern Europe (2%) 45,70 . Two articles reported on patients from more than one country 24,45 …”
Section: Resultsmentioning
confidence: 99%
“…Socio‐cultural variables related to longer patient intervals were explored in four articles and included vague symptom interpretation, 58 lack of knowledge about cancer and cancer symptoms, not believing that cancer is curable, being unfamiliar with breast self‐examination, 52 and use of complementary or alternative medicine 60 . One article documented effects of fear of cancer, spouse behavior, and carelessness on the patient interval but did not specify the direction or meaning of the effects (e.g., whether fear of cancer was related to longer or shorter patient intervals) 59 …”
Section: Resultsmentioning
confidence: 99%
“…Delay in the diagnosis and treatment of BC is a major challenge that can lead to disease progression and develops mortality and also reduces the survival rate of patients; so; timely diagnosis of the disease is an important factor to prevent the mortality of BC. [ 5 ] BC screening is one of the best methods to decrease mortality through early diagnosis of disease. [ 6 ] There have been different methods recommended for BC screening, including mammography, Clinical Breast Exam (CBE), and Breast Self-Exam (BSE).…”
Section: Introductionmentioning
confidence: 99%